DINAMIKA BARU PEMILIHAN LOKASI BAGI PERUSAHAAN RITEL SISTEM FRANCHISE - Sujadi, Sujadi (Sekolah Tinggi Ilmu Ekonomi Semarang, 2010)
For retail companies for  expansion  of the franchise   system  is a must  to be done. For that companies  need an appropriate  strategy  to support  the opening  of new  outlets.  Strategies   that  can  be done  in addition  to site  selection   strategy   is qualitati1'ely  Flexible  manufacturing   system  (FMS,  Just-In-Time    (JIT)  and  total quality  management  ( TQM).